2021
DOI: 10.1002/ccd.29458
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors and outcomes of device‐related thrombus after left atrial appendage closure with the WATCHMAN device—Insights from the EWOLUTION real world registry

Abstract: Background In this analysis of the EWOLUTION registry, we evaluated the incidence, relevance and predictors of device‐related thrombus in a large multi‐center real‐world cohort undergoing LAAc with the WATCHMAN device. Methods and Results We analyzed the 835 patients who underwent percutaneous LAA closure with the WATCHMAN device in the EWOLUTION registry in whom at least one TEE follow up was performed. Patients were 74 ± 9 y/o and were at high risk for stroke and bleeding (CHA2DS2‐VASC‐Score 4.3 ± 1.7; HAS‐B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
(34 reference statements)
1
30
0
1
Order By: Relevance
“…Another possible reason that there was no DRT in this study is that the proportion of long-standing AF, an independent factor associated with DRT, was low after AF ablation. 23 The immediate success rate of occlusion was 100% (PDL ≤3 mm), but there were 3 patients with 1-stop LAA closure and ablation who had residual flow >3 mm during follow-up. This may be caused by regression of tissue edema caused by ablation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another possible reason that there was no DRT in this study is that the proportion of long-standing AF, an independent factor associated with DRT, was low after AF ablation. 23 The immediate success rate of occlusion was 100% (PDL ≤3 mm), but there were 3 patients with 1-stop LAA closure and ablation who had residual flow >3 mm during follow-up. This may be caused by regression of tissue edema caused by ablation.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, DRT was most frequently detected within the first 3 months after LAA closure. 23 However, Dukkipati et al 24 reported that late DRT was detected in 27 of 1,504 patients (1.8%) at 12 months. Because the decision in this study on whether to perform subsequent TEE was based on the 3-month follow-up results, the incidence of late DRT may have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariable regression analysis, a history of previous stroke was identified as an independent predictor of DRT ( 30 ). However, in the WOLUTION registry, which contains a high proportion of patients with prior stroke/TIA (30.5%) and a positive detection rate of DRT (4.1%), no data was provided on the impact of history of prior stroke/TIA on occurrence of DRT and the correlation between DRT and future thromboembolic risk ( 32 ). In our cohort, the incidence rate of DRT was in accordance with those of aforementioned studies and did not differ between patients with and without prior stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Søndergaard et al 30 compared two different drug regimens [antiplatelet therapy (APT) vs. oral anticoagulant (OAC)] in the overall population of PROTECT AF and PREVAIL trials, CAP, CAP2, ASAP and EWOLUTION registries and observed a higher DRT rates in the group of patients on the APT regimen compared with those on OAC, but it did not translate into a significant difference in terms of neurological events between the two groups. The 2-year follow-up data of the EWOLUTION registry in 1020 patients showed a lack of significant differences in the annual incidence of thromboembolic events in patients with or without DRT (respectively 1.7% vs. 2.2%, P = 0.805) for the WM device 31,32 …”
Section: Device-related Thrombosis and Outcomesmentioning
confidence: 99%